2021
DOI: 10.1039/d0ma01008a
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the influence of natural deep eutectic solvents (NaDES) in the properties of chitosan-stabilised films

Abstract: In the present work, the plasticising effect of the natural deep eutectic solvents (NaDES) choline chloride/lactic acid and betaine/lactic acid in the formation of chitosan-stabilised films is investigated. The films...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…The conductive properties of chitosan increased with the addition of DESs ChCl/lactic acid, taking into account the increased charge carrier density in the film, which showed that the chitosan/DES electrolytes are of great practical implications for the design of flexible and biobased supercapacitors (Vorobiov et al., 2021). In addition to ChCl‐based DESs, the plasticizing effect of DESs ChCl/lactic acid and betaine/lactic acid or as separate components in the formation of chitosan‐based films was compared (Pontillo et al., 2021). The thickness and weight of the films increase with the concentration of the DESs.…”
Section: Dess As Components Used In Polysaccharide‐based Packagingmentioning
confidence: 99%
See 1 more Smart Citation
“…The conductive properties of chitosan increased with the addition of DESs ChCl/lactic acid, taking into account the increased charge carrier density in the film, which showed that the chitosan/DES electrolytes are of great practical implications for the design of flexible and biobased supercapacitors (Vorobiov et al., 2021). In addition to ChCl‐based DESs, the plasticizing effect of DESs ChCl/lactic acid and betaine/lactic acid or as separate components in the formation of chitosan‐based films was compared (Pontillo et al., 2021). The thickness and weight of the films increase with the concentration of the DESs.…”
Section: Dess As Components Used In Polysaccharide‐based Packagingmentioning
confidence: 99%
“…The water vapor permeability of the film treated by the DESs (7.0–12.5 × 10 −9 g/Pa s m) increases more than the films with acetic acid (about 3.0 × 10 −9 g/Pa s m). Especially, the films prepared by DESs were significantly different from those treated by simple mixtures of DES compositions (Pontillo et al., 2021).…”
Section: Dess As Components Used In Polysaccharide‐based Packagingmentioning
confidence: 99%
“…In a recent study, it was reported that PRO:GLU-based DESs had also a similar behavior and slightly lowered the roughness from 4 to 3 nm in CS membranes [24]. According to Pontillo et al [36], the resultant smoothness of CS membranes doped with DES reveals an existing interaction with the chitosan macromolecule. The low value of roughness in the CS: PRO:XYL membranes allows us to have a perspective of possible hydrophilic membranes.…”
Section: Membrane Characterizationmentioning
confidence: 89%
“…A further paper, in which NADES were used to endow plasticizing properties to chitosan films, was presented by Pontillo et al [105]. The authors investigated the solubility of chitosan in NaDES aqueous solutions of choline chloride: lactic acid (ChCl-LA, molar ratio 1:1.5) and betaine: lactic acid (bet-LA, 1:2), demonstrating that chitosan can be dissolved in 1% NaDES w/v water solutions.…”
Section: Nades In the Pharmaceutical Fieldmentioning
confidence: 99%